Curable resin composition for flexible film coating
Patent Information
- Application Number
- CN202580021716.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2025-02-26
- Publication Date
- 2026-10-30
AI Technical Summary
[0020]若为本发明的实施方式的可挠性膜涂布用固化性树脂组合物,则能够形成弯曲性及耐擦伤性优异的固化膜。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention relates to a curable resin composition for coating flexible films. Background Technology
[0002] It is known to use curable resin compositions that can be cured by irradiation with active energy rays such as ultraviolet light as coating agents for protecting the surface of a film. For example, Patent Document 1 discloses a curable resin composition comprising a specific urethane (meth)acrylate and a reaction product of a polyfunctional (meth)acrylate and a polyfunctional thiol.
[0003] In recent years, flexible displays, which can be repeatedly bent and used, have become increasingly popular, for example in display applications. Flexible displays include foldable displays, which can be folded, and rollable displays, which can be rolled into a cylindrical shape, and are used, for example, in portable electronic devices such as smartphones or tablets.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-113414 Summary of the Invention
[0007] The technical problem that the invention aims to solve
[0008] In the optical films used in flexible displays as described above, the coating film formed on the surface is required to be flexible enough not to produce streaks even when repeatedly bent, and also to be resistant to damage even when the surface is rubbed, i.e., scratch resistance. Generally speaking, scratch resistance tends to be improved by increasing the surface hardness, but if the hardness is increased, flexibility and bendability tend to decrease, making it difficult to balance bendability and scratch resistance.
[0009] In view of the above, the object of embodiments of the present invention is to provide a curable resin composition for flexible film coating that can form a curable film with excellent flexibility and abrasion resistance.
[0010] Technical means for solving problems
[0011] The present invention includes the embodiments shown below.
[0012] [1] A curable resin composition for flexible film coating, comprising:
[0013] A urethane (meth)acrylate, which is a reaction product comprising pentaerythritol (meth)acrylate with a hydroxyl value of 150 mgKOH / g to 240 mgKOH / g and an aliphatic polyisocyanate; and
[0014] Tetrafunctional thiols.
[0015] [2] The flexible film coating curable resin composition as described in [1], wherein the above-mentioned tetrafunctional thiol compound comprises a tetrafunctional thiol compound derived from pentaerythritol.
[0016] [3] The flexible film coating curable resin composition as described in [1] or [2], wherein the mass ratio of the above-mentioned urethane (meth) acrylate to the above-mentioned tetrafunctional thiol compound is 90 / 10 to 98 / 2.
[0017] [4] The flexible film coating curable resin composition as described in any one of [1] to [3], wherein the above-mentioned pentaerythritol (meth)acrylate is a mixture of pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate and pentaerythritol tetra(meth)acrylate.
[0018] [5] Use of a curable resin composition for coating flexible films, wherein the curable resin composition comprises: urethane (meth) acrylate, which is a reaction product of a raw material comprising pentaerythritol (meth) acrylate with a hydroxyl value of 150 mgKOH / g to 240 mgKOH / g and an aliphatic polyisocyanate; and a tetrafunctional thiol compound.
[0019] Invention Effects
[0020] If the flexible film coating curable resin composition is the embodiment of the present invention, a cured film with excellent flexibility and scratch resistance can be formed. Detailed Implementation
[0021] The flexible film coating curable resin composition of this embodiment (hereinafter referred to as "curable resin composition") comprises the following components (A) and (B).
[0022] (A) Ingredients: urethane (meth) acrylate, which is a reaction product containing pentaerythritol (meth) acrylate with a hydroxyl value of 150 mgKOH / g to 240 mgKOH / g and aliphatic polyisocyanate.
[0023] (B) Components: Tetrafunctional thiol compounds.
[0024] In this specification, the term "(meth)acrylate" refers to acrylates and / or methacrylates. The term "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid. The term "(meth)acryloyl" refers to an acryloyl group and / or a methacryloyl group.
[0025] [(A) Ingredient: Carbamate (meth)acrylate]
[0026] As component (A), urethane (meth) acrylate is obtained by reacting pentaerythritol (meth) acrylate with a hydroxyl value of 150 mgKOH / g to 240 mgKOH / g with aliphatic polyisocyanate as the essential raw material. The hydroxyl groups contained in pentaerythritol (meth) acrylate react with the isocyanate groups of aliphatic polyisocyanate to form urethane bonds.
[0027] (Pentaerythritol (meth)acrylate)
[0028] In this embodiment, pentaerythritol (meth)acrylate with a hydroxyl value of 150 mgKOH / g to 240 mgKOH / g is used as the raw material (reaction component) for component (A). By keeping the hydroxyl value below 240 mgKOH / g, the decrease in the scratch resistance of the cured film can be suppressed. By keeping the hydroxyl value above 150 mgKOH / g, the cured film can be easily stretched, and the formation of streaks due to repeated bending can be suppressed. The hydroxyl value of pentaerythritol (meth)acrylate is preferably 155 mgKOH / g to 230 mgKOH / g, more preferably 180 mgKOH / g to 230 mgKOH / g.
[0029] In this specification, the hydroxyl value is determined according to JIS K0070-1992. Specifically, the sample (pentaerythritol (meth)acrylate) is dissolved in acetic anhydride / pyridine (15 parts by mass / 85 parts by mass). After reacting at 90°C for 1.5 hours, a small amount of water is added, and the reaction is continued for another 10 minutes, followed by cooling to room temperature. Then, phenolphthalein is added as an indicator, and the hydroxyl value is determined by titration with a 1 mol / L potassium hydroxide (KOH) ethanol solution.
[0030] Pentaerythritol (meth)acrylate is obtained by reacting pentaerythritol with (meth)acrylic acid, wherein the hydrogen atom of the hydroxyl group of pentaerythritol is replaced by a (meth)acryloyl group. The hydroxyl value corresponds to the number of substituted hydroxyl groups. The reaction between pentaerythritol and (meth)acrylic acid can be carried out by known methods. Thus, pentaerythritol mono(meth)acrylate (formed by adding one (meth)acrylic acid), pentaerythritol di(meth)acrylate (formed by adding two (meth)acrylic acids), pentaerythritol tri(meth)acrylate (formed by adding three (meth)acrylic acids), and pentaerythritol tetra(meth)acrylate (formed by adding four (meth)acrylic acids) can be formed, typically a mixture containing two or more of these (meth)acrylates. Furthermore, pentaerythritol tetra(meth)acrylate does not have hydroxyl groups and therefore does not react with aliphatic polyisocyanates, but in this embodiment, pentaerythritol tetra(meth)acrylate is also included as a raw material (reaction component).
[0031] In this embodiment, pentaerythritol (meth)acrylate is preferably a mixture of pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate. In one embodiment, 100% by mass of pentaerythritol (meth)acrylate preferably comprises 5% to 35% by mass of pentaerythritol di(meth)acrylate, 35% to 55% by mass of pentaerythritol tri(meth)acrylate, and 20% to 45% by mass of pentaerythritol tetra(meth)acrylate, more preferably comprising 10% to 30% by mass of pentaerythritol di(meth)acrylate, 40% to 55% by mass of pentaerythritol tri(meth)acrylate, and 25% to 40% by mass of pentaerythritol tetra(meth)acrylate. The content of pentaerythritol mono(meth)acrylate can be, for example, less than 5% by mass, or 0% to 3% by mass.
[0032] In this embodiment, the component reacting with the aliphatic polyisocyanate may be only pentaerythritol (meth)acrylate with a hydroxyl value of 150 mg KOH / g to 240 mg KOH / g, but other hydroxyl-containing components such as polyols may also be included as long as the effect is not impaired. In a preferred embodiment, the hydroxyl-containing component comprises 90% by mass or more of the aforementioned pentaerythritol (meth)acrylate. That is, it is preferable that 90% by mass or more of the aforementioned pentaerythritol (meth)acrylate is included in 100% by mass of the hydroxyl-containing component.
[0033] There are no particular limitations on other hydroxyl-containing ingredients, such as: dipentaerythritol (meth) acrylate, glycerol (meth) acrylate, trimethylolpropane (meth) acrylate, di-trimethylolpropane (meth) acrylate, etc.
[0034] (Aliphatic polyisocyanate)
[0035] In this embodiment, an aliphatic polyisocyanate is used as the raw material (reaction component) for component (A). By using a urethane (meth)acrylate obtained by reacting an aliphatic polyisocyanate with a pentaerythritol (meth)acrylate having the specific hydroxyl value described above, the scratch resistance of the cured film can be improved.
[0036] Examples of aliphatic polyisocyanates include: hexamethylene diisocyanate (HDI), pentamethylene diisocyanate, tetramethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, and other aliphatic diisocyanates, as well as their isocyanurate esters, urethane esters, and adducts. Any one of these can be used, or two or more can be used in combination.
[0037] In this embodiment, the component reacting with pentaerythritol (meth)acrylate may be only an aliphatic polyisocyanate, but other polyisocyanates may also be included as long as the effect is not impaired. In a preferred embodiment, the polyisocyanate contains 90% by mass or more of an aliphatic polyisocyanate (preferably hexamethylene diisocyanate). That is, it is preferable that the polyisocyanate contains 90% by mass or more of an aliphatic polyisocyanate within 100% by mass of the polyisocyanate.
[0038] Other polyisocyanates are not particularly limited, but can include, for example: toluene diisocyanate, diphenylmethane diisocyanate, xylene diisocyanate, polyphenylmethane polyisocyanate, phenyl diisocyanate, naphthalene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, or their isocyanurates, urethanes, adducts, etc.
[0039] The reaction of the raw materials containing the above-mentioned pentaerythritol (meth)acrylate and aliphatic polyisocyanate can be carried out by known methods and is not particularly limited. From the viewpoint of the hardness and safety of the cured film, the feed ratio of pentaerythritol to aliphatic polyisocyanate, expressed as the molar ratio of hydroxyl (OH) to isocyanate group (NCO) ([OH] / [NCO]), is preferably, for example, 1.01 to 1.30, more preferably 1.05 to 1.20.
[0040] The content of the above-mentioned pentaerythritol (meth) acrylate and aliphatic polyisocyanate in the raw materials, based on the combined amount of the two, is preferably 80% or more by mass relative to 100% by mass of the raw materials (reaction components), more preferably 90% or more by mass, and even more preferably 100% by mass.
[0041] During the reaction, polymerization inhibitors that hinder the polymerization of (meth)acryloyl groups may also be added. Examples of polymerization inhibitors include: p-benzoquinone, naphthoquinone, toluenequinone, 2,5-diphenyl-p-benzoquinone, hydroquinone, 2,5-di-tert-butylhydroquinone, methylhydroquinone, mono-tert-butylhydroquinone, hydroquinone monomethyl ether, 2,6-di-tert-butylcresol, p-tert-butylcatechol, etc.
[0042] During the reaction, a catalyst may also be added to promote the reaction. Examples of catalysts include: dibutyltin dilaurate, dibutyltin diacetate, tin octoate, zinc hexanoate, cobalt naphthenate, triethylamine, triethylenediamine, bismuth nitrate, bismuth bromide, and 1,8-diazabicyclo[5,4,0]undecene.
[0043] Alternatively, organic solvents such as ethyl acetate, butyl acetate, methyl ethyl ketone, and toluene can also be used in the reaction.
[0044] [(B) Component: Tetrafunctional thiol compound]
[0045] In the curable resin composition of this embodiment, a tetrafunctional thiol compound is incorporated as component (B). During curing of the curable resin composition, the thiol group (SH) of the tetrafunctional thiol compound reacts with the carbon-carbon double bond of the urethane (meth)acrylate to form a CS bond. By incorporating a tetrafunctional thiol compound into the aforementioned specific urethane (meth)acrylate, flexibility and scratch resistance can be improved.
[0046] Tetrafunctional thiols are compounds having four thiol groups within their molecules. Preferably, the tetrafunctional thiols contain tetrafunctional thiols derived from pentaerythritol. The tetrafunctional thiols derived from pentaerythritol are esters of a fatty acid (preferably a saturated fatty acid) with thiol groups and pentaerythritol. The fatty acid with thiol groups preferably has 2 to 5 carbon atoms, more preferably 2 to 4.
[0047] In one embodiment, the compound represented by the following general formula (1) is preferably used as the tetrafunctional thiol compound.
[0048] [Chemistry 1]
[0049]
[0050] In the formula, R 1 ~R 4Each alkyl group independently represents an alkyldiyl group having 1 to 4 carbon atoms, more preferably an alkyldiyl group having 1 to 3 carbon atoms. The thiol group can be a primary thiol group bonded to a primary carbon, a secondary thiol group bonded to a secondary carbon, or a tertiary thiol group bonded to a tertiary carbon, preferably a secondary thiol group. That is, the tetrafunctional thiol compound can be a primary thiol, a secondary thiol, or a tertiary thiol, preferably a secondary thiol.
[0051] Specific examples of tetrafunctional thiols, as compounds represented by the above general formula (1), include, for example, pentaerythritol tetra(mercaptoacetate), pentaerythritol tetra(3-mercaptopropionate), pentaerythritol tetra(3-mercaptobutyrate), etc. Any one of these or a combination of two or more may be used. Among these, pentaerythritol tetra(3-mercaptobutyrate) is particularly preferred.
[0052] The tetrafunctional thiol compound as component (B) is preferably a tetrafunctional thiol compound derived from pentaerythritol containing 70% by mass or more (preferably a compound represented by general formula (1)), more preferably 80% by mass or more, even more preferably 90% by mass or more, and may also be 100% by mass.
[0053] [Curing Resin Composition]
[0054] The curable resin composition of this embodiment contains the urethane (meth) acrylate as component (A) and the tetrafunctional thiol compound as component (B), and is an active energy ray curable resin composition that can be cured by irradiation with active energy rays.
[0055] In this curable resin composition, the mass ratio (A) / (B) of urethane (meth)acrylate as component (A) to tetrafunctional thiol compound as component (B) is preferably 90 / 10 to 98 / 2. By setting this mass ratio (A) / (B) to 90 / 10 or higher, the effect of improving scratch resistance can be improved. By setting this mass ratio (A) / (B) to 98 / 2 or lower, the effect of improving flexibility can be improved. This mass ratio (A) / (B) is more preferably 92 / 8 to 97 / 3, and even more preferably 93 / 7 to 96 / 4.
[0056] The content of component (A) in the curable resin composition is not particularly limited. The amount of component (A) in 100% by mass of solid components can be 70% to 98% by mass, 80% to 97% by mass, or 90% to 96% by mass.
[0057] The curable resin composition may consist solely of urethane (meth)acrylate and tetrafunctional thiols, and preferably also contains a photopolymerization initiator. Examples of photopolymerization initiators include: phenylalkyl ketone-based photopolymerization initiators such as 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methylphenylacetone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, benzyl dimethyl ketal, and benzoyl isopropyl ether; and acylphosphine oxide-based photopolymerization initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide. Any one of these or a combination of two or more may be used.
[0058] The content of the photopolymerization initiator is not particularly limited. For example, relative to the total mass of components (A) and (B) above, 100 parts by mass, it can be 0.1 to 20 parts by mass, 0.5 to 10 parts by mass, or 1 to 5 parts by mass.
[0059] The curable resin composition may also contain organic solvents as needed to adjust the viscosity during coating. Examples of organic solvents include: alcohols such as methanol, ethanol, propanol, n-butanol, and isobutanol; ketones such as acetone, methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone; cellosols such as ethyl cellosol; aromatics such as toluene and xylene; glycol ethers such as propylene glycol monomethyl ether; acetates such as methyl acetate and ethyl acetate; and diacetone alcohol. Any one of these organic solvents may be used, or a combination of two or more may be used.
[0060] In addition to component (A), the following may also be incorporated into this curable resin composition, without impairing the effects of this embodiment: urethane (meth)acrylates other than component (A), vinyl unsaturated monomers other than urethane (meth)acrylates, thiols other than tetrafunctional compounds, acrylic resins, surface conditioners, leveling agents, polymerization inhibitors, fillers, dyes, pigments, oils, plasticizers, waxes, desiccants, dispersants, wetting agents, gelling agents, stabilizers, defoamers, surfactants, thixotropic agents, antioxidants, flame retardants, antistatic agents, matting agents, crosslinking agents, silica, zirconium compounds, preservatives, etc.
[0061] This curable resin composition can be used to coat flexible films and protect the surface of the flexible film. After being coated onto a substrate of the flexible film, the curable resin composition can be cured by irradiation with active energy rays, forming a cured film on the substrate surface. If the curable resin composition contains an organic solvent, it can also be cured by irradiation with active energy rays after drying to remove the organic solvent following coating.
[0062] As a substrate for flexible films, there are no particular limitations as long as it has the flexibility to be bent repeatedly. Examples include resin films and glass films containing polyester resins, polyimide resins, polyolefin resins, polycarbonate resins, acrylonitrile butadiene styrene copolymer (ABS), polystyrene resins, etc.
[0063] In this specification, "film" also includes sheets. The thickness of the substrate of the flexible film such as the resin film or glass film is not particularly limited, for example, it can be 10 μm to 250 μm, 20 μm to 100 μm, or 30 μm to 80 μm.
[0064] There are no particular limitations on the coating method of this curable resin composition. Examples include wet coating methods such as spraying, gravure, dipping, roller coating, rotary coating, and screen printing.
[0065] The active energy rays used to cure the curable resin composition coated on the substrate include, in addition to far-ultraviolet, ultraviolet, near-ultraviolet, and infrared rays, electromagnetic waves such as X-rays and gamma rays, electron rays, proton rays, and neutron rays. Among these, curing by ultraviolet irradiation is preferred. In this case, for example, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, metal halide lamps, xenon lamps, and LED lamps can be used to irradiate with 30 mJ / cm² light. 2 ~3,000 mJ / cm 2 It is cured by ultraviolet light.
[0066] The thickness of the cured film formed using this curable resin composition is not particularly limited; for example, it can be 1 μm to 10 μm or 2 μm to 5 μm.
[0067] The hardness of the cured film is not particularly limited. According to JIS K5600-5-4:1999, the pencil hardness can be above 3 H, or it can be 3 H to 5 H.
[0068] Flexible films having a cured film formed from the curable resin composition of this embodiment can be used for various applications. Examples include: optical films for flexible displays, films for vehicle interiors or exteriors, decorative films for building materials, etc. Among these, optical films for flexible displays are particularly preferred.
[0069] The term "optical film for flexible displays" refers to an optical film used in flexible displays that are repeatedly bent. Examples of flexible displays include foldable displays, which are foldable displays, and rollable displays, which can be rolled into a cylindrical shape. Examples of flexible displays assembled into portable electronic devices such as smartphones or tablets include flexible displays.
[0070] Example
[0071] The present invention will be described in detail below based on embodiments and comparative examples, but the invention is not limited thereto.
[0072] The following are examples of the synthesis of pentaerythritol acrylate 1 to pentaerythritol acrylate 3.
[0073] [Pentaerythritol acrylate 1]
[0074] (Pentaerythritol acrylate with a hydroxyl value of 205 mgKOH / g)
[0075] 1151 parts by mass (16.0 mol) of acrylic acid, 604 parts by mass (4.44 mol) of pentaerythritol (Perstorp's "Pentaerythritol mono"), 43.9 parts by mass of p-toluenesulfonic acid, 2.1 parts by mass of hydroquinone monomethyl ether, and 552 parts by mass of toluene were added to a four-necked flask equipped with a thermometer, stirrer, and water-cooled condenser, and mixed. The reaction was then carried out under reduced pressure, with air purging to maintain the reaction temperature at approximately 100°C, until 56% of the total hydroxyl groups in the pentaerythritol were esterified. The reaction was carried out while removing condensation water. After the reaction was complete, 353 parts by mass of toluene were added. Neutralization was performed by adding a 20% by mass aqueous solution of sodium hydroxide, equivalent to 1.1 moles of the acid content of the reaction solution containing the added toluene, while stirring, thereby removing excess acrylic acid and p-toluenesulfonic acid. Subsequently, the organic layer was separated, and water (10 parts by mass relative to 100 parts by mass of the organic layer) was added while stirring, thereby performing a water washing treatment. The organic layer was then separated again, and toluene was removed by distillation under reduced pressure and heating. The obtained pentaerythritol acrylate 1 was 860 parts by mass, with a hydroxyl value of 205 mgKOH / g.
[0076] The ratios of dimers, trimers, and tetramers of pentaerythritol acrylate 1 obtained by HPLC analysis are as follows.
[0077] Pentaerythritol diacrylate 24% by mass
[0078] Pentaerythritol triacrylate 45% by mass
[0079] Pentaerythritol tetraacrylate 31% by mass
[0080] [Pentaerythritol acrylate 2]
[0081] (Pentaerythritol acrylate with a hydroxyl value of 158 mgKOH / g)
[0082] 1151 parts by mass (16.0 mol) of acrylic acid, 604 parts by mass (4.44 mol) of pentaerythritol (Perstorp's "Pentaerythritol mono"), 43.9 parts by mass of p-toluenesulfonic acid, 2.1 parts by mass of hydroquinone monomethyl ether, and 552 parts by mass of toluene were added to a four-necked flask including a thermometer, stirrer, and water-cooled condenser, and mixed. The reaction was then carried out under reduced pressure, with air purging to maintain the reaction temperature at approximately 100°C, until 68% of the total hydroxyl groups in the pentaerythritol were esterified. The reaction was carried out while removing condensation water. After the reaction was complete, 353 parts by mass of toluene were added. Neutralization was performed by adding a 20% by mass aqueous solution of sodium hydroxide, equivalent to 1.1 moles of the acid content of the reaction solution containing the added toluene, while stirring, thereby removing excess acrylic acid and p-toluenesulfonic acid. Subsequently, the organic layer was separated, and water (10 parts by mass relative to 100 parts by mass of the organic layer) was added while stirring, thereby performing a water washing treatment. The organic layer was then separated again, and toluene was removed by distillation under reduced pressure and heating. The obtained pentaerythritol acrylate 2 was 649 parts by mass, with a hydroxyl value of 158 mgKOH / g.
[0083] The ratios of dimers, trimers, and tetramers of pentaerythritol acrylate 2 obtained by HPLC analysis are as follows.
[0084] Pentaerythritol diacrylate 10% by mass
[0085] Pentaerythritol triacrylate 51% by mass
[0086] Pentaerythritol tetraacrylate 39% by mass
[0087] [Pentaerythritol acrylate 3]
[0088] (Pentaerythritol acrylate with a hydroxyl value of 229 mgKOH / g)
[0089] 1151 parts by mass (16.0 mol) of acrylic acid, 604 parts by mass (4.44 mol) of pentaerythritol (Perstorp's "Pentaerythritol mono"), 43.9 parts by mass of p-toluenesulfonic acid, 2.1 parts by mass of hydroquinone monomethyl ether, and 552 parts by mass of toluene were added to a four-necked flask equipped with a thermometer, stirrer, and water-cooled condenser, and mixed. The reaction was then carried out under reduced pressure, with air purging maintained at approximately 100°C, until 50% of the total hydroxyl groups in the pentaerythritol were esterified. The reaction was carried out while removing condensation water. After the reaction was complete, 353 parts by mass of toluene were added. Neutralization was performed by adding a 20% by mass aqueous solution of sodium hydroxide, equivalent to 1.1 moles of the acid content of the reaction solution containing the added toluene, while stirring, thereby removing excess acrylic acid and p-toluenesulfonic acid. Subsequently, the organic layer was separated, and water (10 parts by mass relative to 100 parts by mass of the organic layer) was added while stirring for washing. The organic layer was then separated again, and toluene was removed by distillation under reduced pressure. The obtained pentaerythritol acrylate 3 was 807 parts by mass with a hydroxyl value of 229 mgKOH / g.
[0090] The ratios of dimers, trimers, and tetramers of pentaerythritol acrylate 3 obtained by HPLC analysis are as follows.
[0091] Pentaerythritol diacrylate 30% by mass
[0092] Pentaerythritol triacrylate 44% by mass
[0093] Pentaerythritol tetraacrylate 26% by mass
[0094] [HPLC Analysis Method]
[0095] The proportions of each component in pentaerythritol acrylate were determined using high-performance liquid chromatography (HPLC, Shimadzu Corporation's "Prominence-iLC2050C"). Specifically, the determination was performed using an Inertsil ODS-2 column (Geel Semiconductor Co., Ltd., 4.6 mm inner diameter × 250 mm length), at a column temperature of 40°C, with a gradient dissolution method using a methanol / water ratio of 20 / 80 to 100 / 0 in the mobile phase.
[0096] Details of pentaerythritol acrylate 4 and pentaerythritol acrylate 5 are as follows.
[0097] • Pentaerythritol acrylate 4: “Aronix M-933” manufactured by Toa Synthetic Co., Ltd., with a hydroxyl value of 280 mg KOH / g.
[0098] • Pentaerythritol acrylate 5: Newfoundland PET-3 manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., with a hydroxyl value of 120 mgKOH / g.
[0099] The following are examples of the synthesis of urethane acrylates UA1 to UA3 and urethane acrylates UAC1 to UAC4.
[0100] [Ultra-urethane acrylate UA1]
[0101] A flask was filled with 21.4 parts by weight of hexamethylene diisocyanate (HDI), 0.05 parts by weight of hydroquinone monomethyl ether as a polymerization inhibitor, 0.02 parts by weight of dioctyltin dineodecanate as a reaction catalyst, and 78.6 parts by weight of pentaerythritol acrylate (acrylate 1) with a hydroxyl value of 205 mgKOH / g (molar ratio [OH] / [NCO] = 1.13). The mixture was then reacted at 50°C–80°C until the free isocyanate content was below 0.1%, thereby obtaining urethane acrylate UA1.
[0102] [Carbamate acrylate UA2 ~ Carbamate acrylate UA3 and Carbamate acrylate UAC1 ~ Carbamate acrylate UAC4]
[0103] As shown in Table 1 below, the type and amount of pentaerythritol acrylate, as well as the type and amount of polyisocyanate, are changed. Otherwise, urethane acrylates UA2 to UA3 and urethane acrylates UAC1 to UAC4 are synthesized in the same manner as urethane acrylate UA1. In Table 1, IPDI represents isophorone diisocyanate as an alicyclic polyisocyanate, and XDI represents xylene diisocyanate as an aromatic polyisocyanate.
[0104] [Table 1]
[0105]
[0106] [Examples 1 to 6 and Comparative Examples 1 to 6]
[0107] Add methyl ethyl ketone to the formulations (parts by mass) shown in Tables 2 and 3 below to prepare a coating liquid (curing resin composition) with a solid component concentration of 40% by mass. Details of the components in Tables 2 and 3, excluding urethane acrylate UA1 to urethane acrylate UA3 and urethane acrylate UAC1 to urethane acrylate UAC4, are as follows.
[0108] • Thiol compound 1: Pentaerythritol tetra(3-mercaptobutyrate), "Karenz MTPE1" manufactured by Rezonack Co., Ltd., a tetrafunctional secondary thiol compound
[0109] • Thiol compound 2: 1,3,5-tris(2-(3-mercaptobutyryloxy)ethyl)-1,3,5-triazine-2,4,6-trione, "Carens MT NR1" manufactured by Rezonack Co., Ltd., a trifunctional secondary thiol compound
[0110] • Polymerization initiator 1: "Omnirad 184" manufactured by IGM Resins BV
[0111] • Polymerization initiator 2: "Omnirad TPO H" manufactured by IGM Resins BV
[0112] The hardness, flexural properties, scratch resistance, and elongation of the coating solution (curing resin composition) obtained above were evaluated. The evaluation method is shown below.
[0113] [Pencil Hardness]
[0114] The coating solution was applied to a glass plate to achieve a dry film thickness of approximately 3 μm, and then dried in an oven at 80°C for 1 minute. Subsequently, under nitrogen conditions, a high-pressure mercury lamp (80 W / cm² × 1 lamp) was used to achieve a cumulative illuminance of 600 mJ / cm². 2 Irradiation was performed to obtain a test piece after the coating had cured. The pencil hardness of this test piece was then measured according to JIS K5600-5-4:1999.
[0115] [Flexibility]
[0116] The coating solution was applied to a 100 μm thick polyethylene terephthalate (PET) film (Toyobo Co., Ltd., "Cosmoshine A4360") with a dry film thickness of approximately 3 μm, and dried in an oven at 80°C for 1 minute. Subsequently, under nitrogen conditions, a high-pressure mercury lamp (80 W / cm x 1 lamp) was used to achieve a cumulative illuminance of 600 mJ / cm². 2 Irradiation is performed to obtain a cured film. The cured film is then tested according to JIS K5600-5-1:1999, and its flexibility is evaluated according to the following criteria. Furthermore, from the viewpoint of flexibility that does not easily produce stripes even with repeated bending, it is preferable that the evaluation is B or higher, and the evaluation of elongation described below is B or higher.
[0117] A: The spindle diameter is 2 mm and no stripes are produced.
[0118] B: The spindle diameter is 2 mm and produces stripes.
[0119] C: The spindle diameter is 3 mm or more and produces stripes.
[0120] [Abrasion Resistance]
[0121] The coating solution was applied to a 100 μm thick PET film (Toyobo Co., Ltd. "Cosmoshine A4360") with a dry film thickness of approximately 3 μm, and dried in an oven at 80°C for 1 minute. Subsequently, under nitrogen conditions, a high-pressure mercury lamp (80 W / cm x 1 lamp) was used to achieve a cumulative illuminance of 600 mJ / cm². 2 Irradiation is performed to obtain a cured film. For the cured film, #0000 steel wool is used under a load of 250 g / cm². 2 A scratch test was conducted under the condition of 1000 round trips at a stroke of 6 cm. The cured film after the test was visually confirmed and evaluated according to the following criteria.
[0122] A: The number of damaged roots is two or less.
[0123] B: The number of damaged roots is three or more but less than four.
[0124] C: The number of damaged roots is five or more.
[0125] [Elongation]
[0126] The coating solution was applied to a 100 μm thick PET film (Toyobo Co., Ltd. "Cosmoshine A4360") with a dry film thickness of approximately 3 μm, and dried in an oven at 80°C for 1 minute. Subsequently, under nitrogen conditions, a high-pressure mercury lamp (80 W / cm x 1 lamp) was used to achieve a cumulative illuminance of 600 mJ / cm². 2 Irradiation was performed to obtain a cured film. A 75 μm thick PET protective film ("KTF" manufactured by Tokyo Film Services Co., Ltd.) was laminated to the back of the cured film. After stamping using a punching machine, the PET protective film was peeled off to create a test piece with a test width of 5 mm and a test length of 30 mm (excluding the gripping portion in the tensile test). A tensile testing apparatus (A1 Co., Ltd.) was used... アンド The test piece (TENSILON ORIENTEC RTC-1225A) manufactured by Dayi was stretched at a test speed of 5 mm / min, and the elongation (mm) at the point when cracks appeared on the surface of the coated film was determined as the measured value. This operation was performed with n=5, and the elongation was calculated by averaging three data points with similar measured values according to the following formula, and evaluated according to the following criteria.
[0127] Elongation = (Average of three similar measurements (mm) / 30 (mm)) × 100 (%)
[0128] A: More than 10%
[0129] B: 8% or more but less than 10%
[0130] C: Less than 8%
[0131] [Table 2]
[0132]
[0133] [Table 3]
[0134]
[0135] The results are shown in Tables 2 and 3. Comparative Examples 1 and 2 are examples of using pentaerythritol acrylate in combination with the reaction product of aliphatic polyisocyanate, namely urethane acrylate, and a tetrafunctional thiol compound. However, in Comparative Example 1, the hydroxyl value of pentaerythritol acrylate was greater than the specified value, resulting in poor scratch resistance. In Comparative Example 2, the hydroxyl value of pentaerythritol acrylate was less than the specified value, resulting in poor elongation and poor flexibility in preventing striations even after repeated bending.
[0136] In Comparative Example 3, the polyisocyanate constituting the urethane acrylate was an alicyclic polyisocyanate, resulting in low hardness and poor scratch resistance. In Comparative Example 4, the polyisocyanate constituting the urethane acrylate was an aromatic polyisocyanate, resulting in poor scratch resistance and flexibility.
[0137] In Comparative Example 5, no thiol compound was formulated, resulting in poor flexibility. In Comparative Example 6, the thiol compound used in conjunction with the urethane acrylate was a trifunctional thiol compound, which exhibited poor scratch resistance.
[0138] In contrast, Examples 1 to 6, which combine pentaerythritol acrylate with a specific hydroxyl value and the reaction product of aliphatic polyisocyanate, namely urethane acrylate and tetrafunctional thiol compound, exhibit excellent scratch resistance, as well as excellent bending and elongation.
[0139] Furthermore, the various numerical ranges described in the specification can be arbitrarily combined with their upper and lower limits, and all such combinations are described in this specification as preferred numerical ranges. Additionally, the description of the numerical range "X~Y" refers to values above X and below Y.
[0140] The foregoing has described several embodiments of the present invention, but these embodiments are provided as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments, or their omissions, substitutions, and modifications, are included in the scope or spirit of the invention, and are similarly included in the scope of the invention described in the claims and their equivalents.
Claims
1. A curable resin composition for flexible film coating, characterized in that, Include: A urethane (meth)acrylate, which is a reaction product comprising pentaerythritol (meth)acrylate with a hydroxyl value of 150 mgKOH / g to 240 mgKOH / g and an aliphatic polyisocyanate; and Tetrafunctional thiols.
2. The curable resin composition for flexible film coating as described in claim 1, wherein, The tetrafunctional thiols include tetrafunctional thiols derived from pentaerythritol.
3. The curable resin composition for flexible film coating as described in claim 1, wherein, The mass ratio of the urethane (meth) acrylate to the tetrafunctional thiol compound is 90 / 10 to 98 / 2.
4. The curable resin composition for flexible film coating as described in claim 1, wherein, The pentaerythritol (meth) acrylate is a mixture of pentaerythritol di(meth) acrylate, pentaerythritol tri(meth) acrylate, and pentaerythritol tetra(meth) acrylate.
Citation Information
Patent Citations
Curable resin composition, and laminate including layer of cured product of the composition
JP2015113414A
